Nilai-Nilai Sufistik Dalam Novel: Analisis Semiotika Pada Penggallah Kepalamu dan Persembahkan Pada Mursyidmu Karya Maya Safira Muchtar - Wahyudi, muhammad Yusril; Malik, Abdul; Tayib, Mukhtar (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2025)
Literature is the expression of thoughts, feelings, and emotions conveyed by the author, resulting in a work that contains elements of beauty. The aim of this study is to explore the Sufistic values in the novel "Penggallah Kepalamu dan Persembahkan pada Mursyidmu" and to examine the critical discourse within the novel. This research is a type of library research, con ducted by collecting data from books, encyclopedias, and other sources deemed relevant to the theme, and falls under the category of text studies. It seeks to identify theories and concepts that serve as the theoretical foundation and help build the theore tical framework for the researcher in analyzing Sufistic values in the novel: a semiotic analysis of "Penggallah Kepalamu dan Persembahkan pada Mursyidmu" by Maya Safira Muchtar. The novel illustrates the presence of numerous symbols and signs whose meanings must be interpreted through semiotic analysis. It narrates the story of a student’s complete self- surrender alongside Anand Krishna, the spiritual guide (mursyid). Maya Safira Muchtar, who spiritually transforms into "Archana" or a sacred offering, undergoes a profound transformation in her life. From a fragile young woman burdened for years by the trauma of sexual abuse at the age of twelve, she evolves into an independent, creative, and compassionate individual. From someone who once harbored anger tow ard God and even despised religion, she becomes someone who is full of faith and capable of feeling divine love.